Reproducibilidad de la escala de Masmali en la valoración de la película lagrimal (2021)
Objective: To determine the inter-rater reproducibility of the Masmali scale based on the Ferning Test for the evaluation of tear film. Materials and methods: An analytical observational study was carried out to evaluate diagnostic tests. The sample consisted of 50 students from the optometry program of the Universidad Santo Tomás, Bucaramanga. The osmolarity of the tear film of the individuals was evaluated through the Ferning test. Two observers classified the fern patterns obtained, using the Masmali scale to determine their reproducibility. Results: the Masmali scale was shown to be a valid tear osmolarity measurement tool; its results are reliable and reproducible. The inter-rater agreement was moderate with a Weighted Kappa of 0.5658 with 88% agreement and a standard error of kappa of 0.0995 and a P value of <0.0001.Conclusions: The Masmali scale based on the Ferning Test proved to be reproducible and reliable considering the results obtained.